Neurobiological and psychological aspects of brain recovery - Petrosini, Laura (Springer, 2017)
The novelty of this book's approach lies in addressing the impact of neurobiological factors as well as psychological influences on brain recovery. There is growing evidence that emotional, motivational, and cognitive factors along with personality traits play a crucial role in brain plasticity, resilience, and recovery. Topics include synaptic and neuronal plasticity, development of brain reserves, biological markers, environmental factors, psychological profile, emotional resilience, and personality traits. By combining the latest research on neural mechanisms and on psychological resilience the authors hope that this book can lead to the development of better treatment strategies for functional recovery from brain damage.
Keywords: Brain -- Wounds and injuries -- Patients -- Rehabilitation.; Brain damage -- Psychological aspects.; Developmental neurobiology.; elektronické knihy; electronic books